Integrating Moroccan Islamic Intellectual Heritage into Contemporary Islamic Education: A Systematic Literature Review - Youssef Chraibi; Aicha Bouzidi (SYAMIL: Journal of Islamic Education, 2025)
This systematic literature review examines the intersection of Moroccan Islamic intellectual heritage and contemporary education. The purpose is to explore how this rich heritage, encompassing philosophy, theology, sciences, literature, and arts, can be integrated into modern educational practices. The methodology involves a comprehensive analysis of scholarly articles, book chapters, and other relevant sources, using a systematic approach to identify, assess, and synthesize existing research. Findings reveal the historical development of Islamic thought in Morocco, highlighting key figures and their contributions, as well as the influence of local traditions. The review explores various types of Islamic educational institutions, curricula, and teaching approaches, along with the roles of governmental and non-governmental organizations. Challenges in contemporary Islamic education, such as the impacts of modernization, globalization, and the integration of traditional values into curricula, are also investigated. The review emphasizes that integrating the Moroccan Islamic intellectual heritage into contemporary education can foster critical thinking, promote moral values, and cultivate respect for cultural and traditional values. This integration holds significant implications for shaping identity, promoting innovation, and enriching the educational experience for students. The originality of this review lies in its comprehensive synthesis of diverse perspectives, providing valuable insights for educators, policymakers, and researchers interested in the revitalization of Islamic intellectual traditions within the context of contemporary education in Morocco.